PERCEPTION OF THE IMPORTANCE OF TEACHING ABOUT LABORATORY ANIMAL SCIENCE TO PROFESSIONALS OF HEALTH GRADUATION COURSES IN SÃO LUÍS – MA, BRAZIL - Dias, H L; Silva, K S M; Paiva, F P; Rossi, M I D (Physiological research, 2023)
In vivo experimental research has existed for centuries and has brought many benefits to human and non-human species. Among those benefits, we can mention the discovery of vaccines, treatments, and knowledge about anatomical features of the various species. However, for many years, experiments were performed without due regulation. In Brazil, with the approval of the Arouca Law (11794/2008), the breeding and use of animals in research, teaching and testing throughout the national territory are now submitted to this Law. Consequently, there was a need to improve aspects and techniques of teaching, breeding and research. Currently, the harmonization of teaching practices and experimental protocols are prioritized. Laboratory Animal Science (LAS) is a multidisciplinary subject and like other areas is in the search of improvement in skills and competencies. The aim of this research was to evaluate the degree of knowledge on Laboratory Animal Science of future teachers, researchers, and health professionals in the state of Maranhao, Brazil, since this discipline is not offered in normal curricular courses. Questionnaires were applied to 249 students from three Universities in Maranhao: students of biomedicine, biological sciences, pharmacy, medicine, and veterinary. The results demonstrate that the careers which are the focus of this research show fragile training in the area of Laboratory Animal Science (LAS) with little knowledge about technical responsibilities concerning breeding facilities and animal research. It was concluded that LAS needs to be a mandatory curriculum discipline for the courses of Biological Sciences and Veterinary and an elective course for Biomedicine, Pharmacy, and Medicine in order to give these professionals enough knowledge to better work in research, teaching, and testing when using experimental animals.